EFEKTIVITAS PROJECT BASED LEARNING TERHADAP KETERAMPILAN MENULIS BAHAN AJAR IPA CALON GURU SD - Susilawati, -; Jannah, Widia Nur; Dianasari, - (Universitas Pendidikan Indonesia, 2018)
Abstract:. The purpose of this research is to analyze the effectiveness of Project Based Learning (PjBL) of writing skills on Science teaching materials to elementary school teachers candidates.This research used experimental methods (single-one group pretest-posttest design) with instruments such as portofolio assessment sheets, observation sheets, andÂ questionnaire sheets .The effectiveness of analyzing used n-gain and t-test .The subject of this research is elementary school teachers candidates who contracted â€œScience Learningâ€subjectÂ in a program study teacher education of elementary school at University Muhammadiyah Cirebon. The findings of this study has produced a contextual book for Science teaching material. In addition, there is an increased of elementary school teachers candidates who prepared the teaching materials in a printed form relevant to the needs and characters of the students as well as the curriculum. It is proven by assessments that the ability rose significantly from 2,71 (categoryÂ is adequate skill) to 3,83 (category is skilled) and supported by the n-gain valueÂ at 0,87. Based on the t-test count of 8,050 larger than t-table 2,045. Recommendations from this research is that PjBL as a learning model could become one of the alternative learning models to improve writing skills material for elementary school teachers candidates.Keyword: Project-Based-Learning, science-materials-teaching, elementary-schoo-teachers- candidates.Â Abstrak: Tujuan penelitian ini untuk menganalisis efektivitas Project Based Learning (PjBL) terhadap keterampilan menulis bahan ajar IPA Calon Guru SD. Penelitian ini menggunakan metode eksperimen (Single-One Group Pretest-Posttest Design) dengan menggunakan instrumen berupa lembar penilaian portofolio, lembar observasi, dan lembar angket. Efektivitas dianalisis menggunakan n-gain dan uji T. Subjek penelitian ini adalah mahasiswa calon guru yang mengontrak matakuliah Pembelajaran IPA di Program Studi Pendidikan Guru Sekolah Dasar (PGSD) Universitas Muhammadiyah Cirebon. Temuan penelitian ini telah menghasilkan buku ajar cetak IPA yang kontekstual. Selain itu, keterampilan calon guru dalam menyusun bahan ajar cetak yang relevan dengan kebutuhan dan karakter siswa serta kurikulum yang berlaku juga meningkat. Hal ini dibuktikan dengan hasil penilaian yang meningkat signifikan dari 2,71 (kategori cukup terampil) menjadi 3,83 (kategori terampil) serta didukung oleh hasil n-Gain yang tinggi yaitu 0,87. Selain itu berdasarkan uji T diketahui bahwa t hitung sebesar 8,050 lebih besar dari t tabel yaitu 2,045. Rekomendasi dari penelitian ini model PjBL dapat dijadikan salah satu alternatif model pembelajaran untuk meningkatkan keterampilan menulis bahan ajar mahasiswa calon guru SD.Kata Kunci: Project-Based-Learning, Bahan Ajar IPA, Calon Guru SD.